An Invitation to Anthropology : the Structure, Evolution and Cultural Identity of Human Societies. - Llobera Josep R. (Berghahn Books, 2003)
Synthesizing British, French and American traditions, this stimulating and accessible text presents a comprehensive and fascinating introduction to social and cultural anthropology. It offers an original approach through integrating knowledge produced from a variety of perspectives, placing cultural and social anthropology in a wider context including macro-sociological concepts and reference to biological evolution. Written in a clear and concise style, it conveys to the student the complexities of a discipline focusing on the structure, evolution and cultural identity of human societies up to the present day. The text consists of four major parts: the scope and method of anthropology, a conceptual and institutional overview, the evolution of the structure of human societies, and the cultural politics of race, ethnicity, nationalism and multiculturalism.